84 ESTABLISHING A "PEDOMETER PRESCRIPTION" FOR LATINOS WITH TYPE 2 DIABETES. (1st January 2005) - Beale, E. O.; Mathur, R.
Abstract : Purpose: 1.To determine if requesting type 2 diabetics (T2 DM) to add a 30-min walk to their usual daily activity is associated with a significantly higher weekly step-count (SC) as recorded by a lightweight, inexpensive, clip-on pedometer, 2.To determine acceptability of pedometer use to subjects. Methods: Prospective, crossover, 2-week study of sedentary adult T2 DM subjects with no medical contraindication to walking. SC was recorded during a 30-min investigator monitored walk (30-min SC). In week 1, subjects continued with usual activity and recorded their 7-day SC. In week 2, subjects were asked to deliberately include a 30-min. daily walk and again record SC. All subjects wore a 0.75oz, $15, single button, commercially available electronic pedometer clipped to the waistband. This model is reported to be accurate to 6 3% on SC. All subjects completed a short questionnaire relating to pedometer use. Results: See table . Results for 13 subjects are available so far in this ongoing study. All subjects were Latino, 11 female, average age was 54.2 years. The average SC in Week 2 was 33% higher than in Week 1 (2-tailed paired t-test p=0.01). The average daily increase in SC in Week 2 was 78% of that in the 30-min walk (6 23 mins. extra walking/day). However, there was a wide variation in inter-subject SC change. All subjects reported that the pedometer was easy to use and they would like to use it regularly. Conclusions: This small, short-term study demonstrates that requesting Latinos with T2 DM to add 30-min walking to daily activity is associated with an average increase in daily SC similar to that recorded during a monitored 30-min walk. There is however a wide variation between subjects in SC change. We conclude that pedometers provide an acceptable, inexpensive means for patients and healthcare providers to quantify baseline walking activity and monitor progress to achieving recommended daily exercise.